Pelayanan - Riska Amelia; Yetti Meuthia Hasibuan; Denny Walady Utama (Jurnal Industri dan Teknologi Samawa, 2024)
PT. Panorama Destination Medan is a travel agent that has European and Asian markets. This PT is located on Jalan Air Bersih No. 55 Medan. In its services, PT. Panorama Destination always makes every effort to achieve customer satisfaction. However, in the last few months PT. Panorama Destination experienced a decrease in passengers, unlike in previous months, this occurred due to unsatisfactory service for passengers. The aim of this research is to find out what attributes need to be improved. Based on the results of data processing and data analysis that has been carried out, it can be concluded that: Based on calculations carried out to measure the level of service quality provided by PT. Panorama Destination, the results obtained are that the level of service quality that has been obtained does not satisfy passenger expectations, where the Responsiveness dimension has a Negative Gap value which has a satisfaction value of 3.730 and an importance value of 3.738 so it has a Gap value of -0.008 2. From the Dimension that has a negative Gap value, namely Responsiveness then Attributes that must be considered in efforts to increase passenger satisfaction are attributes a. Employees are very responsive in handling passenger complaints b. Employees are always eager to help passengers